Systematic review of multiliteracies skills, multimodal tools to facilitate learning in early childhood classroom - Yakubu, Francis Moodu; Obafemi, Kayode Ezechael (Jurnal Inovasi Teknologi Pendidikan, 2023)
This systematic review of literature investigates the use of multimodal tools and acquisition of multiliteracies skills to facilitate effective learning in early childhood educational settings. The review covered a total of 15 relevant articles obtained from databases such as ERIC, Education Full Text, PsycINFO, and Web of Science. Having analyzed and synthesized the current evidence, the review provides a significant and valuable insight into the use and acquisition of multiliteracies skills and tools to facilitate learning in early childhood settings. The sole purpose of this review is to add to the body of existing literature in multiliteracies. The study also provides answer to the only research question of the review which was what are the most effective ways to implement multiliteracies and multimodal techniques in the classroom and how early childhood education can benefit from the systematic application of multiliteracies and multimodal learning. The result of the review revealed that, teachers are facing greater challenges than ever in choosing and designing a pedagogy that can engage students in meaningful literacy practices due to the changing literacy needs in the multimedia environment, the changing lifeworld's of the learners, and the changing dimensions of school literacies. Therefore, the review recommended that policymakers must work to incorporate all multimodal tools and technology into the curriculum, especially for early childhood education. Also, schools and learning centers should provide limitless opportunities in early childhood classrooms and environment to assist, direct, and motivate students to learn.